FIDIC 2017 : the contract manager's handbook - Smith, Geoffrey (Emerald Publishing Limited, 2024)
FIDIC 2017: The Contracts Manager's Handbook is a practical guide to the effective use of the management procedures within the 2017 FIDIC suite of contracts. The book gives step-by-step guidance through the use of flowcharts, timelines and case studies drawn from the author's experience, showing how to manage the contract effectively, and explaining exactly what is expected of each of the parties and when. Key features of the book * suitable for all levels - for experienced users the book highlights and explains the developments introduced in the latest editions; and for new users the book presents a complete overview and step-by-step guide on using the contracts effectively * clear explanations of contractual provisions behind the procedures and potentially important legal requirements * coverage across the project life cycle, emphasising the importance of the provisions during the pre-contract phase, and procedures for efficient contract management post-contract award * a guide to the second editions of FIDIC Red, Yellow and Silver Books, as well as special provisions imposed by the World Bank and other Multilateral Development Banks, and modifications introduced by the 2022 Reprints. FIDIC 2017: The Contracts Manager's Handbook is an essential companion for all users of the FIDIC 2017 suite of contracts, and in particular for users from any level or position in the management chain, whether Employer, Engineer or Contractor.
Includes index.
Keywords: Contracting out -- Management.; Engineering contracts.; Business & Economics -- Industrial Management.; Management & management techniques.; elektronické knihy; electronic books